2020
DOI: 10.1016/j.heliyon.2020.e04419
|View full text |Cite
|
Sign up to set email alerts
|

The surfactants effect on the heat transfer enhancement and stability of nanofluid at constant wall temperature

Abstract: Surfactants role in the enhancement of the heat transfer and stability of alumina oxide – distilled water nanofluid was introduced in this research, where there are limited studies that conjugate between the stability improvement and its effect on the heat transfer coefficients. Four weight concentrations for the experiment were used (0.1, 0.3, 0.6, and 0.9%) with 20 nm particle size under a constant wall temperature. The selection of appropriate surfactants weight was tested too by implementing three weight c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…The results showed that a maximum of thermal conductivity enhancements of up to 35% with the optimum amount of surfactant. Furthermore, Askar et al [16] also had similar results where nanofluid with surfactant has higher heat transfer enhancement compare without surfactant. Ouikhalfan et al [19] found that TiO2/water with SDS and CTAB surfactants had 10% thermal conductivity enhancement compared with the sample without surfactant.…”
Section: Effect Of Surfactant On Heat Transfer Performancementioning
confidence: 72%
See 2 more Smart Citations
“…The results showed that a maximum of thermal conductivity enhancements of up to 35% with the optimum amount of surfactant. Furthermore, Askar et al [16] also had similar results where nanofluid with surfactant has higher heat transfer enhancement compare without surfactant. Ouikhalfan et al [19] found that TiO2/water with SDS and CTAB surfactants had 10% thermal conductivity enhancement compared with the sample without surfactant.…”
Section: Effect Of Surfactant On Heat Transfer Performancementioning
confidence: 72%
“…The nanofluid prepared manage to stable for 5 weeks. Askar et al [16] had prepared a stable prepared Al2O3/water nanofluid using SDS for 44 days for 1wt% nanoparticle with 0.5wt% surfactant. Das et al [17] had prepared a stable Al2O3/water using SDBS for several hours.…”
Section: Effect Of Surfactant On Nanofluid Stability 311 Ionic Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, sonication is often used after magnetic stirring [96]. Surfactants are a simple method, and effective chemical method applies to reduce the surface tension of the base fluid and improve the immersion of NPs for long term stability [97]. Surfactants are generally divided into four categories based on head composition; namely ionic (long-chain fatty acids, alkyl sulphates, sulfosuccinates, phosphates, and sulfonates), nonionic (polyethylene oxide, alcohols), cationic (longchain quaternary ammonium compounds and long-chain amines), and amphoteric surfactants [98].…”
Section: Sonication Usually Conducted By Either An Ultrasonic Bathmentioning
confidence: 99%
“…Many surfactants have already been tested with various nanoparticles such as Sodium Dodecylbenzene (SDBS) (Wusiman et al, 2013;Estellé et al, 2015;Kim et al, 2018), Sodium Dodecyl Sulphate (SDS) (Kim et al, 2018), Cetyl Trimenthyl Ammonium Bromide (CTAB) (Leong et al, 2016;Choi et al, 2018), Polyvinylpyrrolidone (PVP) , and Gum Arabic (Leong et al, 2016). As reported by Askar et al (2020) and Ma et al (2021), different surfactants can both positively or negatively affect the thermophysical properties of a nanofluid and their efficiency as coolants.…”
Section: Introductionmentioning
confidence: 99%